(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Last two decades have seen intense efforts by governmentto expand the provision and improve the infrastructure for elementary educationin India, complemented by the emergence of increasing and diverse privatesector provisions. The analysis shows that the number of children participatingin elementary education has improved, and the improvements are more visibleamong children from rural areas, educationally lagging states, girls and thosefrom the socially and economically disadvantaged groups.